Pengembangan Media Pembelajaran Website Matematika di Kelas 5 SDN Cikoko 01 Pagi Jakarta - Siti Nurazizah Qurota A'yun; Febrianti Yuli Satryani (Universitas Negeri Padang, 2021)
This research was conducted with the aim of producing a mathematically valid and effective learning website for building mathematical spaces in terms of implementation to increase the learning outcomes of 5th grade students of SDN Cikoko 01 Pagi. This research was conducted using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The website for learning to build a mathematical space gets the final percentage result from media experts with an average of 94% and the category is very valid or very feasible to use. The assessment given by students in the limited-scale trial obtained gets the field-scale of 89% and the category is very good. The use of the mathematics building learning website in spatial building materials has been proven to meet the feasibility aspect for use in learning, and has succeeded in increasing students' learning outcomes of student scores increased by 17.8% from the average pre-test score (before using the media) of 77.2% with the number of students who passed the KKM as many as 8 out of 24 students, to 95% in the post-test scores (after using the media) with a total of 24 out of 24 students passing the KKM.